31.4k views
4 votes
Answer help me please ergent

Answer help me please ergent-example-1
User Dan Manion
by
5.8k points

1 Answer

6 votes

Answer:

x = -2

y = -4

Explanation:

After adding both equations, you would then have

0 + 11y = -44

11y = -44

y = -44/11

y = - 4

Now, you substitute for y in either of the first equations. I'm using the second one.

-3x + 2(-4) = -2

-3x - 8 = -2

-3x = -2 + 8

-3x = 6

x = -6/3

x = -2

Therefore, x = -2 and y = -4

You can test for it by substituting both in the equation

-3(-2) + 2(-4) =

6 - 8 = -2

User Dmitry Druganov
by
5.7k points